PEMANFAATAN MEDIA SOSIAL DI ERA DIGITAL SEBAGAI SARANA PROMOSI MI MUHAMMADIYAH CABANG KOTA UTARA KOTA GORONTALO - Ikhlas Ul Aqmal; Hendra Pratama Danial; Nurfadliah Nurfadliah (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
This community service project aims to enhance the promotional capabilities of MI Muhammadiyah North City Branch, Gorontalo, by utilizing social media in the digital era. The background of this activity stems from the school's lack of popularity amid the increasing competition among educational institutions, compounded by the limited knowledge of teachers regarding digital promotion strategies. The activity was conducted as a one-day seminar using lectures, discussions, and technical assistance methods, including training in creative content production for platforms such as Facebook, Instagram, WhatsApp, and TikTok. The outcomes indicated improved teacher understanding of the importance of school branding through social media and a renewed enthusiasm for implementing digital marketing techniques. This initiative is expected to be a starting point for the continuous implementation of targeted promotional strategies that align with current technological advancements in communication.